2014
DOI: 10.1177/0023677213517500
|View full text |Cite
|
Sign up to set email alerts
|

The retrobulbar sinus is superior to the lateral tail vein for the injection of contrast media in small animal cardiac imaging

Abstract: Cardiac perfusion studies using computed tomography are a common tool in clinical practice. Recent technical advances and the availability of dedicated small animal scanners allow the transfer of these techniques to the preclinical sector in general and to mouse models of cardiac diseases in particular. This necessitates new requirements for contrast injection techniques as a rapid transport of contrast media from the intravenous access to the animal heart. Clinical contrast agents containing high iodine conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Beyond nephrology, there are also other uses, such as contrast media applications in radiological imaging studies, that are critically dependent upon rapid intravenous injection. 42…”
Section: Discussionmentioning
confidence: 99%
“…Beyond nephrology, there are also other uses, such as contrast media applications in radiological imaging studies, that are critically dependent upon rapid intravenous injection. 42…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, other studies have been published comparing the TV and RO administration routes that show similar results when delivering drugs, antibodies or cells in similar situations. [2][3][4][5][6]9 Also, in our hands, RO administration has shown greater consistency regarding donor chimerism levels due to the ease of the technique and the lower rate of failure.…”
Section: Discussionmentioning
confidence: 65%
“…Socher et al found that the RO administration of contrast media for cardiac perfusion studies in mice using computed tomography provided better cardiac imaging results than TV injections. 5 Some researchers have also claimed that RO administration causes less stress to the animals, although it was not until 2008 that Steel et al published some data to support this. The authors performed a direct comparison of TV and RO injections as IV drug delivery routes in mice.…”
mentioning
confidence: 99%
“…the left ventricular ejection fraction 4 , 5 , 22 – 24 . Recently, experimental time-resolved dual-energy imaging techniques have been introduced 25 and a single method for cardiac perfusion imaging became available 26 by using a novel contrast injection technique 27 . Furthermore, several contrast agents have been proposed that selectively accumulate in healthy myocardium.…”
Section: Introductionmentioning
confidence: 99%